Subjectivity and Social Positions Shape Habitability in the Context of Environmental Change: a Qualitative Case Study in Northern Ghana - Merschroth, Simon; Sterly, Harald; Sakdapolrak, Patrick; Abu, Mumuni; Janoth, Jan-Niklas (DIE ERDE – Journal of the Geographical Society of Berlin, 2024)
The loss of habitable land is increasingly recognized in climate risk assessments, mainly stemming from material approaches based on concepts of loss and damage. While this generalizes people’s experience of environmental change and habitability, the lived realities of environmental change impacts are not homogeneous within one place. Adaptation measures building on such homogenous notions of habitability run risk to not only reproduce but also to increase existing inequalities. Contrasting that, the perception of habitability differs between individuals and is thus subject to multiple claims of truth. Our work aims to add to a more nuanced conceptualization of the habitability concept by showing the socially differentiated perceptions of habitability in a given place. We build our work on a qualitative field study in rural Northern Ghana, drawing on an intersectional understanding of habitability. Our results show how the intersection of gender, age, socio-economic status, and household composition translates into social practices that shape a socially differentiated experience of perceived habitability in places exposed to environmental change. This perception is further influenced by the connectivity of places, as well as by very personal notions of habitability related to changes in social networks and aspects of place attachment. Contrasting material and noncontext based understandings of habitability, we conclude that the habitability of a place exposed to environmental change is subjective, characterized through an actor’s position within a social-ecological system. Understanding this position as embedded in space and time, it is the interplay of various social categories and the social practices emerging from them that shape an actor’s position, and perceived habitability. Understanding this, and consequently avoiding generalizing assessments and statements about habitability, is crucial to implementing policies that enable empowering change, rather than reproducing existing inequalities through climate change adaptation. Those affected by environmental change need to be included when defining habitability.